Mindscapes, the geographies of imagined worlds - Slusser, George Edgar; Rabkin, Eric S. (Alternatives., 1989)
This work is comprised of eighteen essays plus four examples from the ninth annual J. Lloyd Eaton Conference on Science Fiction and Fantasy Literature at the University of California, Riverside. The concept of mindscape, Slusser and Rabkin explain, allows critics to focus on a single fundamental problem: "The constant need for a relation between mind and some being external to mind." The essayists are Poul Anderson, Wendy Doniger O'Flaherty, Ronald J. Heckelman, David Brin, Frank McConnell, George E. Slusser, James Romm, Jack G. Voller, Peter Fitting, Michael R. Collings, Pascal J. Thomas, Reinhart Lutz, Joseph D. Miller, Gary Westfahl, Bill Lee, Max P. Belin, William Lomax, and Donald M. Hassler. The book concludes with four authors discussing examples of mindscape. The participants are Jean-Pierre Barricelli, Gregory Benford, Gary Kern, and David N. Samuelson